RANCANG BANGUN SISTEM INFORMASI PAYROLL DAN LAPORAN PPH 21 BERBASIS DESKTOP PADA PT CATERPILLAR INDONESIA BATAM - Narti Eka Putria; Erlin Elisa (Teknik Informatika, 2021)
The development of information technology has created convenience and accuracy in decision making within government agencies and companies. The problem that often arises in a company is about the payroll system, this is a lot we see in electronic and print media there are employees who do demos to demand an increase in salary and no transparency in payroll. The use of computers in any company is very common and ordinary, because there are already many and even all companies use computers as a medium for storing data and controlling data. But the data storage system is still manual for example with Ms. Excell is still lacking in data storage systems. Where so far the recording of the salary of employees is still using the manual system. Given the payroll in a company is an important thing and requires proper handling so that there are no errors in the calculation of employee work hours or extra hours / overtime hours, so we need a system that can overcome these problems. Using VB.Net 2008 Programming can help in making reports that are fast, accurate, timely and also eliminate the constraints that exist in making salary data reports.